PARADIGMA PENELITIAN TAFSIR AL-QUR’AN DI INDONESIA - Gusmian, Islah (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Studies on the works of Quranic exegesis (kitāb al-tafsīr) as developed in literatures have been so far oriented to unveil technical aspects, methods, and characteristics of the works. Works by al-Farmāwī, Yunan Yusuf,Nasrudin Baidan, for example, share a common tendency in their approaches. Despite of the importance of such works, the current studies on the works of tafsīr are still lack of a comprehensive methodology that enables us to figure out epistimelogical and socio-cultural landscapes of a certain work on tafsir. Using a critical discourse analysis and epistemé of journalistic writing model as the basis, this paper attempts to develop a new paradigmatic construction by which any interests, discourses, ideologies and oppositional spirits against sociopolitical facts in tafsīr works are revealed.Keywords: Tafsir, Analisis Wacana Kritis, Teks Kultural